The Effect of Serotonin Inhibition on Initial Microvessel Hemostasis and Platelet Aggregation In Vivo - Bergqvist, D; Arvidsson, S; Esquivel, C O; Lindblad, B; Haglund, U (Thrombosis and Haemostasis, 1983)
The role of serotonin (5-HT) in initial microvascular hemostasis is not fully understood. This study was made to evaluate the effect on hemostatic plug formation and laser-induced arteriolar microembolism of different substances which counteract the effect of 5-HT. Hemostatic plug formation time and stability was measured in the rabbit mesenteric microcirculation and laserinduced embolism in the rabbit ear chamber. Ketanserine, a selective 5-HT2-receptor blocker shortened arteriolar hemostatic plug formation time. Dihydroergotamine, an unselective blocker (with 5-HT- and α-adrenergic receptor affinity) increased venular hemostatic plug formation time and also decreased the hemostatic plug stability. Laser-induced platelet embolism was unaltered after both ketanserine and dihydroergotamine administration. The magnitude of these changes seems to exclude an important effect of 5-HT in initial microvessel hemostasis or on platelet activity.
Keywords: Rabbits; Hemostatic plug; Platelet; Ketanserine; Dihydro; ergotamine